Assessment of left ventricle myocardial performance index (Tei index) by myocardial tissue Doppler imaging and its correlation with serum thyroid-stimulating hormone levels and atherogenic index of plasma in patients of subclinical hypothyroidism - Amratansh Varshney; Satyajit Singh; Amritava Ghosh; Surendra Kumar Naik; Abhishek Kumar; Chandraprakash Thakur; Muneshwar Kumar; Nupur Goyal; Nabodoy Majumder; Rounak Kumar; Muhammad Rihas Rasheed (Heart India)
Background: Subclinical hypothyroidism (SCH) is defined as a state of increased serum thyroid-stimulating hormone (TSH) level with circulating thyroxine (T4) and triiodothyronine (T3) in the population reference range. Patients with SCH have an increased risk of subclinical cardiac dysfunction and dyslipidemia. Objective: The primary objective was to assess the left ventricular myocardial performance index (MPI), i.e., the Tei index which is a marker of global MPI in subclinical hypothyroid patients. There were two secondary objectives. The first was to assess the correlation between Left ventricle (LV) Tei index and serum TSH level in patients with SCH. The second was to measure the atherogenic index of plasma (AIP) in patients with SCH and it is correlation with the Tei index. Materials and Methods: This was a cross-sectional, observational study including 100 subclinical hypothyroid patients. All subclinical hypothyroid patients attending outpatient department underwent screening, detailed history taking, and clinical examination. Patients were analyzed for eligibility of the study. After taking consent, all eligible patients underwent tests for routine blood sampling, lipid profile, thyroid profile, antithyroid peroxidase antibodies, electrocardiography, and echocardiography including tissue Doppler imaging. MPI was calculated for each patient. MPI was correlated with serum TSH levels and also with atherogenic plasma index (AIP) using an appropriate statistical analysis tool. Results: Fifty-three percent of subclinical hypothyroid patients had abnormal lateral and medial Tei index. Fifty-one percent of subclinical patients had abnormal mean Tei index despite normal left ventricle ejection fraction. However, there was no correlation between the Tei index and TSH level. In this study, 48% and 29% of patients had high and intermediate cardiovascular risk, respectively, according to AIP. No statistically significant correlation was observed between the Tei index and atherogenic index of plasma. Conclusion: Subclinical hypothyroid patients have significant subclinical cardiac dysfunction (as determined by the Tei index) and dyslipidemia. AIP may serve as an effective screening method to identify subclinical hypothyroid individuals who are at higher risk of cardiovascular events. Large prospective studies are needed to validate the AIP-TSH-MPI relationship.